ASEAN economic cooperation and integration progress, challenges and future directions - Chia, Siow Yue (Integration through law : the role of law and the rule of law in ASEAN integration, 2015)
"ASEAN economic cooperation and integration have come a long way since the organisation's early days, when cooperation was more political and diplomatic than economic in nature. ASEAN now constitutes the most ambitious organization of regional cooperation in the developing world. This book investigates the economics of various ASEAN and ASEAN-centric economic integration initiatives, focusing in particular on the ASEAN Economic Community (AEC). In addition to assessing the potential effects of the AEC on the economies of the ten ASEAN member-states via changes in trade, foreign direct investment and economic structure, this book underscores the implementation challenges ASEAN faces as it completes the AEC project. It also considers the AEC in the context of the Regional Comprehensive Economic Partnership (RCEP). This comprehensive study is written for academic researchers and students, as well as for policy makers in ASEAN as they chart the future policy path of the region"--Provided by publisher.